2007
DOI: 10.1158/1078-0432.ccr-06-1817
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Clinical Regimen for the Oncolytic Virus PV701

Abstract: Purpose: Previous phase 1 trials of i.v.-administered PV701 have shown this virus to be welltolerated with toxicity primarily associated with the first dose. Our hypothesis, based on preclinical evidence, was that patient tolerability could be improved by slowing the i.v. infusion rate, and that this approach would allow for the safe administration of higher doses. Additionally, this phase 1trial was the first to measure PV701clearance. Experimental Design: For the first dose, a 3-h infusion was used compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 15 publications
0
95
0
1
Order By: Relevance
“…The major limitations of OVs are their poor delivery to metastatic cancer sites with systemic administration and rapid development of neutralizing antibodies. Nevertheless, in the few patients who responded to OVs, the observed clinical benefit was often durable, even after completion of therapy (1). These studies implicate the role of the antitumor immune response in the observed therapeutic effect of OVs and warrant further exploration of OVs as immunotherapeutic, rather than simply lytic, agents.…”
Section: Introductionmentioning
confidence: 91%
“…The major limitations of OVs are their poor delivery to metastatic cancer sites with systemic administration and rapid development of neutralizing antibodies. Nevertheless, in the few patients who responded to OVs, the observed clinical benefit was often durable, even after completion of therapy (1). These studies implicate the role of the antitumor immune response in the observed therapeutic effect of OVs and warrant further exploration of OVs as immunotherapeutic, rather than simply lytic, agents.…”
Section: Introductionmentioning
confidence: 91%
“…NDV preferentially replicates in a variety of human tumor cells but not in normal cells (Reichard et al, 1992). As NDV is nonpathogenic in humans and is associated with only a few minor symptoms, several NDV strains are under clinical evalulation for anticancer treatment (Sinkovics and Horvath, 2000;Pecora et al, 2002;Hotte et al, 2007). The tumor-selective replication of oncolytic RNA viruses such as NDV or vesicular stomatitis virus (VSV) has been proposed to be related to tumor-specific defects in the cellular antiviral defense.…”
Section: Introductionmentioning
confidence: 99%
“…NDV has been shown to possess oncolytic properties (27,32) and has been used as a cancer vaccine and also as an oncolytic agent in several clinical trials in different human cancers (14,16,21,34). The selectivity of NDV and other oncolytic viruses to cancer cells has been proposed to be due to defects in the type I interferon (IFN) response of cancer cells (13,38).…”
mentioning
confidence: 99%